Autobiographical memory retrieval and appraisal in social anxiety disorder. (August 2018) - Moscovitch, David A.; Vidovic, Vanja; Lenton-Brym, Ariella P.; Dupasquier, Jessica R.; Barber, Kevin C.; Hudd, Taylor; Zabara, Nick; Romano, Mia
Abstract: Individuals with social anxiety disorder (SADs; n  = 41) and healthy controls (HCs; n  = 40) were administered the Waterloo Images and Memories Interview, in which they described mental images that they tend to experience in both anxiety-provoking and non-anxiety-provoking social situations. Participants then recalled, in as much detail as possible, specific autobiographical memories of salient aversive and non-aversive social experiences that they believed led to the formation of these images. Audio-recorded memory narratives were transcribed and coded based on the procedure of the Autobiographical Interview, which provides a precise measure of the degree of episodic detail contained within each memory. Participants also rated the subjective properties of their recalled memories. Results revealed that participants across the two groups retrieved equivalent rates of both aversive and non-aversive social memories. However, SAD participants' memories of aversive events contained significantly more episodic detail than those of HCs, suggesting that they may be more highly accessible. Moreover, participants with SAD appraised their memories of aversive experiences as more distressing and intrusive than HCs, and perceived them as having a significantly greater influence on their self-perception. In contrast, no group differences were observed for memories of non-aversive events. Findings have the potential to shed new light on autobiographical memory in SAD, with implications for psychotherapeutic intervention. Highlights: Examined aversive/non-aversive memory retrieval in social anxiety disorder (SAD). SADs and controls equally accessed aversive and non-aversive memories. SADs' aversive memories contained richer episodic detail than those of controls. SADs appraised aversive memories as more distressing, intrusive, and self-relevant. No group differences observed in recall or appraisals of non-aversive memories.